The role of overeducation and horizontal mismatch for gender inequalities in labor income of higher education graduates in Europe - Passaretta, Giampiero [Verfasser]; Sauer, Petra [Verfasser]; Weßling, Katarina [Verfasser]; Schwabe, Ulrike [Verfasser] (My University, 2023)
„Evidence on gender inequality in the labor market is extensive. However, little is known about the potential role of overeducation and horizontal mismatch in explaining women’s labor-market disadvantages. We draw on recent data from the Eurograduate pilot survey to investigate the role of overeducation, field-of-study mismatch and field-specific overskilling for gender gaps in labor income in the European landscape. We found considerable variations in the extent of both gender earning gaps (GEGs) and wage gaps (GWGs) across countries. However, our decomposition analyses show that neither overeducation nor horizontal mismatch contribute to explaining these gender gaps. The lack of mediation seems related to either the absence of gender differences in overeducation and horizontal mismatch, or to the nonexistence of income penalties associated with the mismatch.“ (authors‘ abstract; BIBB-Doku)
Keywords: G 1.2 Arbeitsmarkt; G 1.2.3.1 Potenziale; G 2.4.5 Gender Mainstreaming; I 2.2 Europa; 370; 330; Arbeitsmarkt; Überqualifikation; Hochschulabsolvent; Geschlechterdifferenz; Lohnstruktur; Europa